Comparative analysis on the performance envelope of a three-pad and four-pad active journal bearing. Issue 1 (31st December 2023) - H, Girish; Kumar, Nitesh; Kumar, Shiva; Pai, Raghuvir; A, Ganesha
Abstract: Controllable fluid film bearings with the ability to actively modify the operational conditions of rotor bearing systems possess high demand in the field of rotating machinery. Controllable or active bearing geometries can effectively enhance the performance envelope and life of machine support systems. Alternate forms of an active bearing pad geometry with unique adjustability features having the ability to modify the rotor bearing performance are presented in this study. The adjustability mechanism incorporated in the active pad geometry allows the multiple-bearing pads to translate radially and undergo tilted motions on a real-time basis. These pad adjustments are simulated by incorporating the radial and tilt adjustable functions into the developed theoretical model. In this study, a major focus is on a three-pad active bearing geometry and will further compare its steady state and dynamic performance behavior with a four-pad active bearing model. Effect of varying pad positions, pad angles and number of pads on the steady state and dynamic characteristics are analyzed in this study. For various combinations of operating parameters, pads adjusted to negative radial and negative tilt position were found to provide a notable improvement in the steady state and dynamic performance parameters. Identifying the optimal pad adjustments will further help to develop an active bearing with a feedback control mechanism operated on a real-time basis.